Pengembangan Sikap Tanggung Jawab Peserta Didik Melalui Pendidikan Karakter Pada Mata Pelajaran PKN Kelas IV UPTD SDN 122380 Pematangsiantar - ; Melisa Nur Asima Sidabutar (LPPM Universitas Buana Perjungan Karawang, 2025)
The purpose of this research is to find out the development of responsibility attitudes through PPKn subjects, to find out the effectiveness of PPKn in instilling character values, especially responsibility attitudes and to know the supporting and inhibiting factors in the development of responsibility attitudes. This research was carried out at UPTD SDN 122380 Pematang siantar. The research will be conducted from August 2024 to September 2024. The research method used is descriptive with a qualitative approach. This study uses interview, observation and documentation data collection techniques. The data analysis technique used is triangulation. The results of the study show that teachers instill a sense of responsibility by integrating character values with the matei taught, the development of responsibility attitudes through PPKn is proven to be effective, the supporting factors for character development are the commitment of the principal, the role of teachers as role models, and support from parents. The inhibiting factors in the development of responsibility attitudes are lack of student awareness, time limitations, and an unsupportive environment.